Hello :
<span>f(x) = 6 – 5x and g(x) = 4x – 1
f(x)-g(x) = 6-5x-(4x-1) = 6-5x-4x+1 = -9x+7
whene x = - 2
f(x)-g(x) = -9(-2)+7 = 25......(answer : D)</span>
Answer:
in my opinion is the last:
this studies uses a control group
Step-by-step explanation:
Gradient of line,m=(17-6)/(20-0)=11/20
finding equation of line using a point (20,17)
y-17=11/20(x-20)
y-17=(11/20x)-11
y=11/20x+(17-11)
y=(11/20)*x+6
Answer:
see explanation
Step-by-step explanation:
The meaning of n factorial → n !
n ! = n(n - 1)(n - 2)........ × 3 × 2 × 1
For example
7 !
= 7 × 6 × 5 × 4 × 3 × 2 × 1